Prestational and sanitary impact of financing capitated in gestants and children under 5 years old in peru, 2011-2014 - Romero-Onofre, Roberto (2018)
Objective: To analyze the impact of the capital on the health of pregnant women and children under 5 years ofage affiliated to comprehensive health insurance in 3 pilot regions between 2011 and 2014. Methods: Study ofcounterfactual analysis of difference in differences. The pilot regions are Apurímac, Ayacucho and Huancavelica,while Amazonas, Cajamarca and Huánuco are controls. Indicators of acute diarrheal disease, acute respiratoryinfection and anemia in children, and of maternal death avoided in pregnant women were measured, andproduction indicators that include coverage of control of growth and development of the child and prenatalcontrol. Results: A negative impact was observed in acute diarrheal disease (-330) and maternal death prevented(-213), and positive in acute respiratory infections (1540), anemia (736) and the child's control and developmentrates and prenatal control - constant (9.5% and 7.8%). Only maternal death avoided was not significant (p =0.21). Conclusion: The expected impact of the capita agreement on acute diarrheal diseases is observed, but noton the other indicators because the capitated increased the opportunity of access and detection of morbidity,increasing the latter.Key words: Capitated; Payment mechanisms; Impact; Difference in differences; Health outcomes; Intermediaryoutcomes; Public insurance system. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1583